2008
DOI: 10.3758/mc.36.6.1168
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting is effortful: Evidence from reaction time probes in an item-method directed forgetting task

Abstract: Reaction time (RT) was measured in response to visual detection probes embedded within an item-method directed forgetting paradigm. In Experiment 1, study words were presented individually followed by an instruction to remember (R) or forget (F). Probes were presented at stimulus onset asynchronies (SOAs) of 1,400, 1,800, or 2,600 msec in relation to the study word or memory instruction. After the study trials, a yes-no recognition task measured retention of R and F words. Experiment 2 added a no-word control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
202
6
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(228 citation statements)
references
References 59 publications
16
202
6
4
Order By: Relevance
“…Consistent with findings reported by Fawcett and Taylor (2008; for further discussion, see , fewer false alarms were made following forget than following remember instructions. Combined with an overall tendency for RTs to be slower following forget than following remember instructions, this suggests that memory instructions may involve a conservative criterion shift.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with findings reported by Fawcett and Taylor (2008; for further discussion, see , fewer false alarms were made following forget than following remember instructions. Combined with an overall tendency for RTs to be slower following forget than following remember instructions, this suggests that memory instructions may involve a conservative criterion shift.…”
Section: Discussionsupporting
confidence: 80%
“…One is led to believe that maintenance rehearsal simply ceases and no other cognitive operations are performed on these representations, such that they decay passively from memory. An alternative to this "rehearsal ceases" view, which conceptualizes forgetting as the result of a passive decay process, is the "attentional withdrawal" view, which conceptualizes forgetting as the result of an active cognitive-control process (e.g., Fawcett & Taylor, 2008Zacks, Radvansky, & Hasher, 1996). According to the attentional withdrawal view, selective rehearsal of remember items can occur because active control mechanisms are engaged to prevent irrelevant forget information from having continued access to limited-capacity working memory resources.…”
Section: Introductionmentioning
confidence: 99%
“…By this view, until participants receive the cue to remember or forget, subjects intentionally halt elaborative encoding until they know what they are supposed to do, elaborating the item further only if it is to be remembered (e.g., Basden, Basden, & Gargano, 1993 ). Others have argued for a role of cognitive control and response override in this procedure (Hourihan & Taylor, 2006 ) , a hypothesis supported by both behavioral (Fawcett & Taylor, 2008 ) and imaging studies ( Wylie, Fox, & Taylor, 2008 ) that document the dependency of the forget instruction on attention and cognitive control systems. Regardless of which mechanism is at play, this task best captures situations in which we may prematurely terminate thoughts about an unpleasant experience to limit the footprint of that experience in our memories.…”
Section: Integration With Research On Directed Forgettingmentioning
confidence: 96%
“…Several behavioural and neural investigations merge to support these two theories. For instance, providing support for the inhibitory account, behavioural evidence has shown that implementation of a cue to forget is more cognitively demanding than a cue to remember, with fewer resources available to perform a secondary task following a forgetrelative to remember-cue (Fawcett & Taylor, 2008).…”
Section: Introductionmentioning
confidence: 99%